2021
DOI: 10.1021/acs.analchem.0c05372
|View full text |Cite
|
Sign up to set email alerts
|

Toward High Spatially Resolved Proteomics Using Expansion Microscopy

Abstract: Expansion microscopy (EM) is an emerging approach for morphological examination of biological specimens at nanoscale resolution using conventional optical microscopy. To achieve physical separation of cell structures, tissues are embedded in a swellable polymer and expanded several fold in an isotropic manner. This work shows the development and optimization of physical tissue expansion as a new method for spatially resolved large-scale proteomics. Herein we established a novel method to enlarge the tissue sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…For benchmarking, we used the well-established in-solution digestion and the pressure cycling technology (PCT)-assisted tissue digestion methods, which are widely used for tissue treatment in MS-based proteomics analysis 21 . While we were finalizing this study, Drelich et al published a conceptually similar method 9 , which we also used for side-by-side comparison with ProteomEx. Since the described method is based on the original protein-retention ExM protocol reported by Tillberg et al 5 , we refer to it as proExM-MS for convenience.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For benchmarking, we used the well-established in-solution digestion and the pressure cycling technology (PCT)-assisted tissue digestion methods, which are widely used for tissue treatment in MS-based proteomics analysis 21 . While we were finalizing this study, Drelich et al published a conceptually similar method 9 , which we also used for side-by-side comparison with ProteomEx. Since the described method is based on the original protein-retention ExM protocol reported by Tillberg et al 5 , we refer to it as proExM-MS for convenience.…”
Section: Resultsmentioning
confidence: 99%
“…While this manuscript was in preparation, Drelich et al reported conceptually similar approach for spatially resolved proteomics 9 , which we refer to as proExM-MS for short. Although both proExM-MS and ProteomEx share the same method for sample magnification based on proExM 5 , they differ in several aspects crucial for their applicability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry (MS)-based proteomics has been demonstrated to characterize >10 000 proteins in human tissues without the requirement of antibodies. 6 To enable spatial proteomics analysis of tissue sections, several microsampling approaches have been developed, 7 including manual dissection, 8 solvent extraction, 9,10 in situ digestion with microdroplet [11][12][13][14] or hydrogel, [15][16][17][18] and laser capture microdissection (LCM). [19][20][21][22][23] The coupling of these microsampling approaches with nanoscale liquid chromatography-mass spectrometry (LC-MS) has enabled the proteome profiling of ∼500 proteins from tissue regions as small as 0.1 mm 2 and 10 μm thickness in diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is through innovations in sample preparation, for example, expansion microscope (ExM) (19)(20)(21), which embeds the specimen into a hydrogel that could expand four times when dialyzed in water, realizing ~70-nm resolution. The ExM technique does not require special machinery or particular data processing, therefore providing affordable approaches for superresolution imaging in most laboratories (22)(23)(24)(25)(26)(27)(28), and has been applied in neuroscience, pathology, and mRNA discovery (29)(30)(31)(32)(33)(34)(35)(36). However, current ExM methods only manage to reach a resolution of about 70 nm, which still lags behind that in modern superresolution instruments (4,16,37,38).…”
Section: Introductionmentioning
confidence: 99%